The effects of music and gender difference on attention and memory test performance among undergraduates in Malaysia: a feasibility study - Lee, Areal Romie; Gwee, Fernanda Qing Err (2019)
A feasibility study was conducted to determine the applicability of CANTAB on examining the effects of different stimuli (music) on attention and memory performance of Malaysian undergraduates. In a repeated-measures design, 13 undergraduates completed two CANTAB test, PAL and RVP in silence and while listening to self-selected music and 15 Hz alpha brainwave music. The results of the current study have supported alternative hypotheses that there are no significant differences between attention and memory in three different conditions. Participants were more distracted in self-selected music condition. Furthermore, significant difference in gender was also not found among undergraduates on attention and memory tests performance. In conclusion, this study suggested that the CANTAB is not feasible to measure the attention and memory tests performance in different music settings. Thus, future researchers were suggested to look on others more useful measurements or assessments to further investigate the related study. The discussion highlighted the theory of capacity model of attention.